Genetic testing in bleeding disorders - de Brasi, Carlos Daniel (2014)
The aim of molecular genetic analysis in families with haemophilia is to identify the causative mutation in an affected male as this provides valuable information for the patient and his relatives. For the patient, mutation identification may highlight inhibitor development risk or discrepancy between different factor VIII assays. For female relatives, knowledge of the familial mutation can facilitate carrier status determination and prenatal diagnosis. Recent advances in understanding mutations responsible for haemophilia and methods for their detection are presented. For reporting of such mutations, participation in external quality assessment ensures that essential patient and mutation details are routinely included and that pertinent information is incorporated in the interpretation.